Accuracy of growth chart use in monitoring and assessing under-nutrition in Kenya. (24th May 2012) - Wright, CM; Mutoro, AN
Abstract : Aims: To find out how well healthcare workers in Kenya plot and interpret information on growth charts. Methods: Doctors and clinical officers (12), nurses, nutritionists and community health care workers (27) who were actively involved in growth monitoring were surveyed at primary care clinics around Nairobi, Kenya in June 2011. They completed questionnaires which included plotting of weights at ages 2, 6 and 9 months using the road to health chart (RTH) currently in use in Kenya and interpretation of 8 plotted scenarios permutated through 2 versions of the questionnaire, with each respondent rating two growth trajectories from a well baby clinic and two for children being treated for malnutrition. Results: There were high levels of plotting errors; up to 78% (29) plotted weights less than 0.5 kg and 41% (16) plotted ages more than 0.5 months from the true value. This seemed to reflect the difficulty of plotting on the RTH chart. Nurses and nutritionists were rather more accurate in plotting charts compared to doctors and clinical officers. From the well-baby clinic scenario, 30% (18 out of 60) correctly identified a slow weight trajectory (fall of 2 weight SD) while 65% (11 out of 17) recognised steady growth. In the malnutrition clinic scenarios 39% (15 out of 39) recognised catch up growth (rise of 1 weight SD). For children seen in well baby clinics 70% (41 out of 59) recognised the need to offer extra care to a child with slow weight gain but 57% (9 out of 16) stated extra care was needed for a small child who had been growing steadily (−2 SD). For the malnutrition clinic scenario, 94% (36 out of 38) healthcare workers recognised that a child without catch up required extra care, but 72% (32 out of 39) also felt this was needed in a child with catch up growth. Conclusion: Growth charts were not plotted accurately, partly due to poor chart design. Healthcare workers did not seem to discriminate between size and weight gain, with the result that they seemed to be concerned about healthy growth patterns when seen in relatively small children.